Migration-induced subjective social mobility and its associations with self-rated mental and general health: a systematic review and narrative synthesis - Platz Pereira, Maike; Gottlieb, Nora; Hintermeier, Maren; Nutsch, Niklas; Bozorgmehr, Kayvan (Social science & medicine, 2025)
Social mobility affects health, but comprehensive evidence on its health effects in migration contexts is lacking. This systematic review summarizes the global empirical quantitative evidence on the impact of migration-induced subjective social mobility on self-rated health outcomes among first-generation migrants, including internally displaced people, international and internal migrants. A systematic search was performed in three scientific databases, using search terms related to migrants, social status/mobility and health outcomes. Studies were included if migrant populations, quantitative measures of health outcomes and subjective social mobility were reported. In total, 13 records met all criteria, representing five different country contexts and covering international migrants, asylum seekers, refugees, and rural-to-urban migrants. Applying cross-sectional study designs, the main outcomes assessed were general health, subjective wellbeing/life satisfaction and depression. The overall evidence shows that downward subjective social mobility consistently correlates with negative mental health effects, namely depression, while upward social mobility is associated with better mental health outcomes. Similar tendencies were found for general health and life satisfaction. The results indicate that downward subjective social mobility is associated with poorer general health, lower life satisfaction and higher risk of depression across various contexts. Correspondingly, upward subjective social mobility and social mobility belief is associated with better general health, higher life satisfaction and lower risk of depression. These findings highlight the need for policies that support post-migration socioeconomic integration to prevent or mitigate the experience of downward mobility and its adverse health effects. Future research is needed to better understand pathways and interactions between policies, contexts, and individual trajectories influencing migration-induced social mobility.
Gesehen am 29.01.2026